Research on composite manufacturing method of semi-buried 1×32 optical splitter - Tao, Qing; Xie, Sihao (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
In this paper, a composite manufacturing method was proposed to reduce the inner surface roughness of silica groove. Firstly, femtosecond laser was used to ablate the silica groove, then, a 5% concentration hydrofluoric acid solution was used to corrode the inner surface of silica groove. Secondly, Su8 adhesive was filled with the groove to form a semi-buried 1×32 optical splitter by doctor blade. The test results showed that the surface roughness Ra was less than 0.2 µm, and average insertion loss of output ports was 21.34 dB, moreover, the uniformity was less than 1.44 dB. Compared with the traditional femtosecond laser ablating method, surface roughness reduced by at least 0.1 µm, and the average insertion loss of output ports was reduced by 1.22 dB, and the uniformity was reduced by 0.41 dB. So, the composite manufacturing method improved the communication performance. It is satisfied with the requirements for optical interconnection in the electro-optical printed circuit boards.
Optica Applicata, Vol. 53, 2023, nr 2, s. 185-195
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; optical splitter; composite manufacturing method; EOPCB